Novel framework for modelling the cadmium balance and accumulation in farmland soil in Zhejiang Province, East China: Sensitivity analysis, parameter optimisation, and forecast for 2050. (10th January 2021) - Fu, Tingting; Zhao, Ruiying; Hu, Bifeng; Jia, Xiaolin; Wang, Zhige; Zhou, Lianqing; Huang, Mingxiang; Li, Yan; Shi, Zhou
Abstract: Modelling the mass balance and forecasting the temporal variations of cadmium (Cd) in farmland soil play a critical role in the development of mitigation strategies for Cd pollution. In this study, a novel framework integrating the mass balance model with model-independent parameter estimation, geostatistics, and bagging algorithms were integrated to simulate the long-term changes in the Cd content of farmland soil in Zhejiang Province, China. The predicted Cd content in farmland soil in 2013 was compared to observed data (R value = 0.568 and root-mean-square error = 0.177 mg kg −1 ), demonstrating the feasibility of our model. The prediction results for 2050 indicated that the average concentration of Cd in farmland soil from Zhejiang Province will increase to 0.30 mg kg −1 if the current trend continues, and that 37.4% of the farmland soil in the province will be classified as a "security utilisation region", indicating great risk of soil Cd contamination in these areas. Reducing industrial emissions and soil acidification to reduce the Cd pollution risk should receive great attention. This study provides a new perspective for forecasting the temporal trends of Cd accumulation in farmland soil and facilitates improved management and risk prevention of Cd pollution in agricultural soils and products. Graphical abstract: Image 1 Highlights: A novel framework was proposed to model cadmium accumulation in farmland soil. Sensitivity analysis was used to identify most impact parameters for prediction. The model had R value of 0.568 and RMSE of 0.177 mg kg −1 validated by data of 2013. Simulations were employed and averaged to produce the final forecast map. Cd in farmland soil in Zhejiang Province will increase to 0.30 mg kg −1 in 2050.